2008
DOI: 10.4314/tjpr.v7i4.14699
|View full text |Cite
|
Sign up to set email alerts
|

Effects of <i>Cassia occidentalis</i> aqueous leaf extract on biochemical markers of tissue damage in rats

Abstract: Purpose: Among the Hausas of Northern Nigeria, it is claimed by local (traditional) healers that the infusion of C. occidentalis leaves is used as a cure for hepatitis. This study was designed to evaluate the possible negative effects of the aqueous extract of this herb on serum total proteins, albumin, bilirubin, alanine amino transferase (ALT), aspartate amino transferase (AST) and alkaline phosphatase (ALP), as part of a larger study undertaken by these authors to ascertain the hepatoprotective potential of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 8 publications
0
18
2
Order By: Relevance
“…The identified plant barks were observed to be rich in diverse chemical constituents (Table 3), widely referred to as phytochemicals [19,20]. Previous assertion by Tapsell et al [21] revealed that plants have the ability to synthesize a wide variety of compounds of medicinal values out which about12, 000 of such compound have been isolated.…”
Section: Ijppe Volume 12mentioning
confidence: 99%
“…The identified plant barks were observed to be rich in diverse chemical constituents (Table 3), widely referred to as phytochemicals [19,20]. Previous assertion by Tapsell et al [21] revealed that plants have the ability to synthesize a wide variety of compounds of medicinal values out which about12, 000 of such compound have been isolated.…”
Section: Ijppe Volume 12mentioning
confidence: 99%
“…The plant contains abundant phenolic and flavonoidal compounds and is often used in the region to treat diarrhea and fever as well as increase milk production in lactating women [9,10]. C. occidentalis, called Sanga-Sanga in northern Nigeria, has alkaloids, phlobatannins, tannins, flavonoids, saponins, terpenes, etc., and is used to treat leg pains, swollen feet, and hepatitis, among others [10][11][12]. Z. mauritiana is called Magarya in Hausa and is rich in alkaloids, flavonoids, tannins, steroids, and saponins [13].…”
Section: Introductionmentioning
confidence: 99%
“…Though some studies had been carried out in this regard, their results are inconsistent. For example, while Nuhu and Aliyu [11] reported hypoproteinemia and elevated liver enzymes in rats fed with extracts of C. occidentalis, Silva et al [15] found no effects of short-and long-term administration of C. occidentalis in treated rats. Vashishtha et al [16] also linked the consumption of C. occidentalis beans to the outbreak of the hepatomyoencephalopathy syndrome among children in western Uttar Pradesh.…”
Section: Introductionmentioning
confidence: 99%
“…This implies that the toxic effect of the pesticides resulted in a noticeable decrease in the serum total proteins and albumin and the administration of the extract tends to normalize the decrease of serum total protein and albumin. Previous studies have reported that induction of toxicant have a negative effect on the serum total proteins and albumin leading to a decrease in the concentration levels (Nuhu and Aliyu, 2008). Bilirubin is the major breakdown product that results from the destruction of old red blood cells.…”
Section: Groupmentioning
confidence: 99%
“…It has been reported that when a toxicant is induced, it leads to hyperbilirubinaemia (high level of bilirubin) which is often the first and sometimes the only manifestation of a liver disease (Nuhu, 2008). Also, the low level of malondialdehyde (Table 6) in the treatment groups which were treated with 200 and 400 mg/kg of L. guineensis seed aqueous.…”
Section: Groupmentioning
confidence: 99%